The genera Allophrys Förster and Aneuclis Förster (Hymenoptera: Ichneumonidae: Tersilochinae) of Vietnam - Khalaim, Andrey I. (Zootaxa, 2018)
Four species of the genus Allophrys Förster, A. daklaka sp. nov., A. davichia sp. nov., A. occipitata Khalaim and A. tonkina sp. nov., and three species of Aneuclis Förster, A. achterbergi sp. nov., A. devriesi sp. nov. and A. secunda (Khalaim), comb. nov., are found to occur in Vietnam. Allophrys daklaka is also recorded from Indonesia. Male of A. secunda is recorded for the first time. This is the first record of the genus Aneuclis from Vietnam and Oriental region. Identification keys to Vietnamese species of Allophrys and Aneuclis are provided. The genus Sathropterus Förster is synonymized with Aneuclis Förster (syn. nov.), and its two species are transferred to the genus Aneuclis: A. pumilus (Holmgren), comb. nov. and A. secunda (Khalaim), comb. nov.